2022
DOI: 10.3389/fmicb.2021.748779
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities and Prediction of Microbial Metabolic Pathway in Rice Wine Koji From Different Regions in China

Abstract: Rice wine koji, a traditional homemade starter culture in China, is nutritious and delicious. The final quality of rice wine koji is closely related to the structure of its microbial community. However, the diversity of natural microorganisms in rice wine koji from different regions has not been evaluated. In this study, the microbial population of 92 naturally fermented rice koji samples collected from Hubei, Guangxi, and Sichuan was systematically analyzed by high-throughput sequencing. From all the rice win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…Moreover, LAB play critical roles in the production of proteins and metabolites such as esterases, lipases, and alcohol acetyl transferases that reportedly contribute to the formation of flavor-related components of wine [10]. Among the prevalent LAB genera, Weissella showed the highest abundance, especially in YC1, YC2, and XG starters, consistent with previous studies that found Weissella is the dominant genus in rice wine koji [6], although other studies have identified Bacillus as a dominant genus among starter microbiota [1]. In addition, Weissella is a representative genus in CSRW starters of Hubei province, which was consistent with previous studies that showed Weissella was a representative genus in Wheat Qu of Hubei province [13].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, LAB play critical roles in the production of proteins and metabolites such as esterases, lipases, and alcohol acetyl transferases that reportedly contribute to the formation of flavor-related components of wine [10]. Among the prevalent LAB genera, Weissella showed the highest abundance, especially in YC1, YC2, and XG starters, consistent with previous studies that found Weissella is the dominant genus in rice wine koji [6], although other studies have identified Bacillus as a dominant genus among starter microbiota [1]. In addition, Weissella is a representative genus in CSRW starters of Hubei province, which was consistent with previous studies that showed Weissella was a representative genus in Wheat Qu of Hubei province [13].…”
Section: Discussionsupporting
confidence: 90%
“…Hierarchical clustering of the CSRW starter samples based on the abundance of bacterial and fungal genera showed similar results to the PCoA plot (Figure 4C,D). Taken together, these results showed that the microbial communities of CSRW starters from different regions exhibited both variability and similarities, which was consistent with findings in previous analyses of CSRW starters [1,6]. The close position among samples indicated similarities in the composition of principal genera, while more distant samples in the PCoA plot reflected differences in these principal genera.…”
Section: Beta Diversity Analysis Of Different Starterssupporting
confidence: 90%
See 1 more Smart Citation
“…BR14 is considered a probiotic Saccharomyces cerevisiae that can significantly increase alcohol content and total acidity. Additionally, cofermentation of BR14 can significantly reduce the urea content of EC formation . Yuan et al.…”
Section: Brewing Of Crwmentioning
confidence: 99%
“…Additionally, cofermentation of BR14 can significantly reduce the urea content of EC formation. 56 Yuan et al. isolated a yeast strain (YB-12), for which the gene sequence was highly similar to that of Meyerozyma , and found that YB-12 could significantly reduce the content of fusel alcohols in CRW.…”
Section: Brewing Of Crwmentioning
confidence: 99%